Evaluation and improvement of protocols for Ganoderma boninense protoplast isolation and regeneration - Anis Farhan Fatimi Ab Wahab,; Madihah Ahmad Zairun,; Khairunnisa Hanisah Mohd Daud,; Farah Diba Abu Bakar,; Izwan Bharudin,; Abdul Munir Abdul Murad, (Penerbit Universiti Kebangsaan Malaysia, 2022)
Ganoderma boninense is the causal agent of basal stem rot (BSR) disease of oil palm. The BSR disease reduces oil palm yield by up to 80% of the average oil yield. Attempts to control the disease caused by this fungus in the field showed varying levels of success and cases of infection increased from year to year. Hence, the development of new efficient methods to control the spread of this fungus should be commenced promptly. To ensure a better strategy is created, more thorough research on the method deploy by this fungus to infect the host at the molecular level need to be carried out first. However, the major limitation in endeavoring into the functional analysis of virulence genes related to the pathogenicity of this fungus was hampered by the unavailability of established methods for protoplast isolation with a high regeneration rate to be used in the genetic manipulation analysis. Thus, in this paper, we report an efficient protocol for protoplast isolation and regeneration in G. boninense and successfully used the isolated protoplasts in PEG-mediated transformation analysis. A large quantity of protoplast was obtained using the protocol that utilizes the following parameters: 3 to 4-day-old mycelia, treated with 1% lysing enzyme and 0.02% Driselase, incubated at 30 °C in an osmotic medium containing 0.6 M mannitol at pH 5.8 for 2 h. The highest protoplast yield was in the range of 8.95 × 109 to 3.12 × 1010 cells/mL per 5 g of mycelia used. The regeneration rate ranged from 9.03% to 22.55%, depending on the regeneration media used. By using 5 μg of vector to transform into 1.0 × 107 protoplast/mL, around 3 – 10 mitotically stable putative transformants were successfully obtained and verified via PCR. This protocol will find useful applications in genetic studies to enhance insight into this poorly characterized and understood phytopathogen.